The Water-Soluble Chitosan Derivative, N-Methylene Phosphonic Chitosan, Is an Effective Fungicide against the Phytopathogen Fusarium eumartii - Mesas, Florencia Anabel (2021)
Chitosan has been considered an environmental-friend-ly polymer. However, its use in agriculture has not been extended yet due to its relatively low solubility in water. N-Methylene phosphonic chitosan (NMPC) is a water-soluble derivative prepared by adding a phosphonic group to chitosan. This study demonstrates that NMPC has a fungicidal effect on the phytopathogenic fungus Fusarium solani f. sp. eumartii (F. eumartii) judged by the inhibition of F. eumartti mycelial growth and spore germination. NMPC affected fungal membrane per-meability, reactive oxygen species production, and cell death. Also, this chitosan-derivative exerted antifungal effects against two other phytopathogens, Botrytis cine-rea, and Phytophthora infestans. NMPC did not affect tomato cell viability at the same doses applied to these phytopathogens to exert fungicide action. In addition to water solubility, the selective biological cytotoxicity of NMPC adds value in its application as an antimicrobial agent in agriculture.